Pengaruh Pembiayaan Umkm Dan Modal Terhadap Laba Pada Koperasi Diskoperindag Di Koperasi Konsumen Wanita Anggrek Bulan Mekar Kota Pariaman - Ferdina Ahmad, Nesa; Hans Gery, Mexano; Handayani, Deby (Universitas Sumatera Barat, 2022)
This research aims to analyze the influence of MSME financing and capital on profits in cooperative trade cooperatives (case study of the women's consumer cooperative Orchid Bulan Bloom Kota Pariaman for the 2018-2019 period). This research uses descriptive analytical research with a quantitative approach. The sampling method used in the research was purposive sampling. The data analysis used was panel data regression using the Eviews10 program. From the results of the regression test, it is found that (a) there is an influence of MSME financing on profits, b) there isnt an influence of capital on profits, c) there is an influence of MSME financing and capital on profits. Based on the Adjust R Square value obtained, it is 0,1320. This shows that the contribution of the independent variable to the dependent variable is 13,20% and 86,80% is determined by other variables not analyzed in the model in this study.